Analyzing the Influence of Perception on Disaster Risk Reduction Strategies and Students' Awareness of Disaster - Dyah Ayuluna Saylomita Swandy; Yunus Aris Wibowo; Siti Hadiyati Nur Hafida; Puspita Indra Wardhani (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to assess the effectiveness of disaster risk reduction strategies implemented in schools and the level of disaster awareness among students living in areas with a high potential for eruption. Methodology: The research method used a quantitative approach with descriptive and correlational analysis. The population in this study was all 837 students of SMA N 1 Dukun. The sample in this study comprised 271 students, selected via simple random sampling. Data collection techniques in this study used questionnaires, observations, and interviews. Data analysis in this study used descriptive and inferential statistical techniques. Results: Students' perceptions of the school-established disaster risk reduction strategies were moderate. Meanwhile, students' level of disaster awareness in facing the eruption of Mount Merapi was high. Correlation analysis showed a relatively positive relationship between students' perceptions of disaster risk reduction strategies and students' disaster awareness. Application/Originality/Value: This study revealed that students' perceptions of school strategies remained moderate, with high levels of disaster awareness, likely influenced by direct experience with prior eruptions.